2016
DOI: 10.5812/ijp.5690
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow Up of Physical Growth and Thyroid Hormone Levels in Infants With Congenital Hypothyroidism

Abstract: Background: Congenital hypothyroidism (CH) is one of the major causes of physical and mental disabilities, which are preventable and treatable. This study aimed to investigate physical growth and to evaluate the effectiveness of performed therapeutic interventions on normality of serum T4 and TSH levels in children with CH of Yazd city. Methods: This retrospective cohort study was performed on all neonates with CH, who were born during years 2006 and 2008. The growth pattern of height, weight and head circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According to a study conducted in Japan on 2,341 children with CH, both CH and healthy children had normal height growth ( 33 ). Lotfi et al found no significant difference between the growth patterns of CH and healthy children after five years of age in terms of height, weight, and head circumference ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted in Japan on 2,341 children with CH, both CH and healthy children had normal height growth ( 33 ). Lotfi et al found no significant difference between the growth patterns of CH and healthy children after five years of age in terms of height, weight, and head circumference ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The onset and completion of puberty and achievement of adult height have been found to be normal in these children. [3][4][5] However, delayed diagnosis of congenital hypothyroidism or acquired juvenile hypothyroidism leads to growth retardation. There is a slowing of growth with a downward deviation from the standard growth curve.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have assessed the growth of infants with congenital hypothyroidism detected by neonatal screening. [3][4][5] Few studies have been done to assess the catch-up growth in older children with hypothyroidism. Therefore, author undertook this study to assess the catch-up growth in children with primary hypothyroidism following treatment with thyroxine.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hemiagenesis (THA) is a rare congenital developmental abnormality, where one of the thyroid lobes fails to develop (1). The etiology of THA and other thyroid dysgenesis (TD) is largely unknown (2,3). Thus, factors that disturb the process by influencing the lobulation of the thyroid anlage are yet to be unraveled (4,5).…”
Section: Introductionmentioning
confidence: 99%